Perfil do adoecimento dos trabalhadores de câmpus universitário do interior paulista: análise dos dados de absenteísmo por motivo de doença - Fantazia, Miriam Malacize [UNESP] (2015)
The profiles of illness and death among workers have changed with the introduction of new production and work methods in society, both in private and in public institutions. In public institutions, recent changes, starting in the 90s, include new management and work organization methods that entail better productivity, faster paced work, employee downsizing, temporary staffing and outsourcing, and labor market flexibility among others. As a result, the rates of physical and mental illness among public servants have increased leading to illness-related absence, defined as time off from work due to illness certified by a physician/sick leave. The objective of this study was to establish the profile of illness-related absence among statutory workers of a Brazilian state public university, in 2012. In this cross-sectional study, secondary data extracted from the institution's occupational medical examination systems and medical reports were analyzed using IBM SPSS Statistics software (v.21.0). The results have been reported as simple and cumulative frequencies, associations estimated by chi-square tests, and distribution differences determined by post-hoc Z tests with Bonferroni's correction coefficient. During the study period, 538 workers were on sick leave. Workers consisted of married females aged over 41 years. Most of them had been working on the institution's hospital of clinics for 11-30 years holding intermediate level nursing positions, and had taken leave once. Of these, 11% were provided with job accommodation. The most frequent causes for leaves, which lasted for up to 15 days, were mental/behavioral disorders, and osteomuscular and connective tissue diseases. Statistical analysis demonstrated that some sociodemographic characteristics, such as sex and age, and job characteristics, such as work unit and position, influenced the development of illness, which in turn influenced leave duration and job accommodation ...